Information Registration in Surgical Special Sheets for Discharege Patients in Tehran University of Medical Sciences Teaching Hospitals , 2005 - M Ghazisaeedi; R Sharifian (Tehran University of Medical Sciences, 2008)
Background and Aim: Currently in most hospitals medical mission and medical documents secession don't be notified about any disciplines in the framework of documenting medical data and in parallel the document makers will be overshadowed by non-executing these principles qualitatively and quantitatively(1).Materials and Methods: The above study is a sectional one that describes the situation of recording informational items in the surgical special sheets. In order to collect information collect information from considered sheets, it has been used of 1040 files of hospitalized because of surgery operation in the under study hospitals.Results: The results of the study showed that 67.5% and 53.4% of informational items have not been recorded in nte sheets General and special hospitals. In the operation report sheet more informational items has been recorded in proportion to others which amounts to 59.9%. Informational items related to the tests in the pre operation care sheet, complementary information in the operation report sheets, and after surgery care and observed side-effects in the anesthesia sheet have the most non recording information.Conclusion: The situation of recording informational items in the surgical special sheets in contrast to previous studied samples is not desirable. Regarding to the importance of these sheets and their position in relation to the information recorded in them, it is necessary to take needed measures to remove the factors that result in non recording the informational items.